2002
DOI: 10.1051/0004-6361:20020181
|View full text |Cite
|
Sign up to set email alerts
|

Metal abundances and ionization conditions in a possibly dust-free damped Lyα system at $\mathsf{\vec{z}=2.3}$

Abstract: Abstract.We have obtained a high resolution, high S/N UVES spectrum of the bright QSO HE 2243−6031 to analyze the damped Lyα system (DLA) observed at z = 2.33. We measure column densities for H i, 86. All of these ratios support an environment that is in an early evolutionary stage, where the onset of star formation has begun only shortly before the DLA was observed. We also perform a cloud-by-cloud analysis -without precedent at high redshift -and find a tight correlation of all low-ionization species with re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 52 publications
3
57
0
Order By: Relevance
“…Prochaska & Wolfe (1996) first studied chemical abundance variations in a single DLA, and showed that the chemical abundances were uniform to within statistical uncertainties. Lopez et al (2002) confirmed this finding from analysis of another DLA using Voigt profile decomposition. Petitjean et al (2002) and Ledoux et al (2002b) showed that the depletion patterns in subcomponents were very similar along DLA profiles except in the components where molecular hydrogen is detected and where depletion is larger.…”
Section: Introductionsupporting
confidence: 78%
“…Prochaska & Wolfe (1996) first studied chemical abundance variations in a single DLA, and showed that the chemical abundances were uniform to within statistical uncertainties. Lopez et al (2002) confirmed this finding from analysis of another DLA using Voigt profile decomposition. Petitjean et al (2002) and Ledoux et al (2002b) showed that the depletion patterns in subcomponents were very similar along DLA profiles except in the components where molecular hydrogen is detected and where depletion is larger.…”
Section: Introductionsupporting
confidence: 78%
“…Even though DLA galaxies have H i column densities spanning an order of magnitude and metallicities spread over two orders of magnitude, previous studies show that DLAs have similar abundance ratios suggesting that these protogalaxies have common enrichment histories (Prochaska & Wolfe 2002). In the same way, the abundance patterns of DLA "clouds" for a given system also show uniformity suggesting that the gas of these protogalaxies has a similar enrichment history and uniform differential dust depletion (Prochaska & Wolfe 1996;Lopez et al 2002;Prochaska 2003). If confirmed, these results have important implications for the ISM of high redshift galaxies and the enrichment of gas in the early Universe.…”
Section: Introductionmentioning
confidence: 67%
“…They compared ionic column densities along the observed velocity profile using the apparent optical depth method (Savage & Sembach 1991). Then, Lopez et al (2002) were the first to present a detailed cloud-to-cloud analysis for a z > 2 damped system based on a Voigt profile analysis.…”
Section: Cloud-to-cloud Chemical Variations In Individualmentioning
confidence: 99%
“…Another place we might look for significant gas-phase H 2 formation is in damped Ly (DLA) systems, many of which have low dust abundances (see, e.g., Lopez et al 2002). An interesting example is the absorber at z ¼ 3:025 in the spectrum of Q0347À3819 recently studied by Levshakov et al (2002).…”
Section: Astrophysical Examplesmentioning
confidence: 99%